Analytical Chemistry Laboratory Qualitative Analysis Process Examination: Links Between Experimental Data and Calculations - Alkan, Fatma (Jurnal Ilmiah Peuradeun, 2021)
Analytical chemistry and qualitative-quantitative analysis practices have an important place in chemistry education. Operations such as experimental steps in volumetric analysis, reactions, and determining the amount of matter require problem-solving and higher-order thinking skills due to mathematical calculations. Students have difficulty and anxiety in making calculations in the volumetric analysis. This research aimed to examine the ability of chemistry teacher candidates to use the data obtained from the neutralization titration experiments in the calculation of the experimental result and to analyze the effects of information obtained from experiments on solving volumetric analysis problems. The sample of the study consisted of 13 chemistry teacher candidates studying in the chemistry teaching program of a state university. The research employed a descriptive survey model. Experiment data sheets and question solutions were taken as written answers. As a result of the research, it is noteworthy that the teacher candidates have problems in calculating the results of the experiment, and this has been overcome with increasing applications.